Supply Chain Manager's Problem-Solver: Maximizing the Value of Collaboration and Technology, The - Poirier, Charles (CRC Press, 2009)
The true promise and benefits of Supply Chain Management elude many organizations. Cultural limitations, a narrow view of the opportunities offered by and the need to access external resources juxtaposed with a lack of understanding of how technology can enhance business processes create resistance. The Supply Chain Manager's Problem-Solver: Maximizing the Value of Collaboration and Technology explores the benefits of a full network approach and illustrates specific actions that lead to success. The author uses case studies to validate the concepts and solutions, provides an easy to understand and apply methodology for getting to higher levels of progress, and explores areas of potential technology application that often get overlooked.